Methodical Approach to Identifying Buying Motives within Various Sales Channels Based on Behavioral Segmentation - DEPUTATOVA, Yelena Yuryevna; URYASEVA, Tatyana Ivanovna; CHEGLOV, Vyacheslav Petrovich; LEONOVA, Julia Gennadievna; BASKAKOV, Vladimir Anatolyevich (Journal of Advanced Research in Law and Economics; Vol 10 No 2 (2019): JARLE Vol X Issue 2(40) Spring 2019DO - 10.14505//jarle.v10.2(40).10, 2020)
The methods for identifying differences in the buying motives in online and offline trade are developed based on a theoretical analysis of approaches to the customer segmentation and their dependence on its purpose. The purpose of the study is to identify differences in the buying motives in online and offline trade and to substantiate the feasibility of conducting behavioral segmentation in order to identify such differences. The empirical research results are based on the quantitative marketing research (polls). The buying motives in offline and online sales channels were studied in several stages. The key advantages of offline and online sales channels were identified in terms of customer perception at the first stage. The following advantages were identified in offline and online trade: high quality guaranteed by the seller for buyers with high incomes; accessibility as the speed and convenience of access, price acceptability for buyers with average and below average incomes; and the breadth, depth, and updateability of the product range for all groups. The buying motives in offline and online trade were identified as factors that encouraged buying at the second stage. The polls have shown that key motives for customers to opt for offline sales channels are related to the perception of the aggregate properties of products that exceed the properties of similar products in online sales channels. The main reasons for buying through online sales channels are the following key indicators that determine the quality of the buying service: convenience and speed of purchasing, speed of delivery, and convenient time to receive an order. This study allowed to develop a model for studying the consumer behavior in order to identify the key rational and emotional motives of buying through online and offline sales channels. The information component of this model was based on the marketing research involving the sequential implementation of the following stages: studying the market trends in order to identify changes in the motives of consumer behavior; selecting segmentation criteria and carrying out marketing research; identifying the key benefits of offline and online sales channels in terms of customer perception; identifying and grouping the key motives that guided customers when choosing a channel for buying; identifying the causes of changes in the rational and emotional motives of consumer behavior; and developing and implementing the marketing communications programs that implied an impact on the emotional and rational motives.